A review on the crisis of antibiotic resistance and the strategies to combat resistance - S. Niveda; O. M. Fasalu Rahiman; P. K. Sreenadh; M. L. Lal Prasanth (Journal of Current Research in Scientific Medicine)
The discovery of antibiotics has caused a huge impact on the history of the entire health-care system. The irrational and excessive use of antibiotics has become futile and has given rise to another serious issue known as antibiotic resistance, which is now a threat to the health-care sector. Due to this, millions of deaths are occurring worldwide every year as infections are becoming difficult to treat as a result of resistance to the antibiotics that are used to treat them. Thus, the confidence of the global health-care system is ruined. The WHO has recognized antibiotic resistance as a serious issue that needs to be addressed and has declared tackling it a high priority. Even though complete eradication of antibiotic resistance is not possible, the spread and the incidence of resistance can be reduced by taking adequate measures. Combating antimicrobial resistance is, therefore, a prime need of the and various strategies have been adopted globally. This article primarily focuses on the phenomenon of antibiotic resistance, the mechanisms of resistance, various reasons that contribute to it, and the strategies adopted to combat the global crisis. Here, we have reviewed articles on antibiotic resistance from scientific websites such as PubMed Central, NCBI, Science Direct, and Google Scholar, and the strategies have been taken from the official website of the WHO, Indian Council of Medical Research, and the guidelines issued on this by the Ministry of Health and Family Welfare Government of India and Government of Kerala.